Take It Slow: can feedback from a smart fork reduce eating speed? - Sander Hermsen; Sander Hermsen (Frontiers Media S.A., 2015)
Background: Reductions in eating rate have been recommended as potential behavioural strategies to prevent and treat overweight [1-4]. Unfortunately, eating rate is difficult to modify, due to its highly automatic nature [5]. Training people to eat more slowly in everyday eating contexts, therefore, requires creative and engaging solutions. Aim: The present study examines the efficacy of a smart fork that helps people to eat more slowly. This adapted fork records eating speed and delivers vibrotactile feedback if users eat too quickly. In two studies, we tested the acceptability and user experience of the fork (Study 1), and its effect on eating rate and satiety levels in a controlled lab-setting (Study 2). Method: In study 1, 11 participants (all self-reported fast eaters) ate a meal using the fork in our laboratory and used the fork for three consecutive days in their home setting. Participants took part in semi-structured interviews after the first meal and upon returning the fork, covering perceived effect on eating rate, comfort of use, accuracy, and motivational and social aspects of fork use. Interviews were coded and a thematic classification analysis was performed. In study 2, 128 participants (all self-reported fast eaters) ate a standardized meal using the fork in our laboratory. We used a between-participants design with 2 conditions; participants ate their meal either with vibrotactile feedback from the fork (experimental condition) or ate their meal without vibrotactile feedback (control condition). Eating rate, meal duration, error rate (number of bites taken faster than 10 seconds after previous bite), total food intake, and satiety were recorded for every participant. Results: Study 1: All participants felt that the feedback was generally accurate and consistent. Fork size, weight, and intensity of the feedback were seen as comfortable and acceptable. All participants reported a heightened awareness of eating rate and all but one participant reported eating more slowly with the fork. Study 2: Participants in the experimental condition ate significantly slower, and with a lower error rate than those in the control condition. Feedback did not significantly affect the amount of food eaten. Conclusions: Our findings suggest that this smart fork is an acceptable and effective tool to disrupt and decelerate eating rate. Participants find the fork comfortable and accurate enough for use in natural contexts, and experimental results show that the fork does influence eating rate, but not the amount of food consumed. Future research should test the long-term effects of fork use on eating rate to assess whether this smart fork indeed leads to sustainable behavioural change.